(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The Internet of Things (IoT) is expanding swiftly and producing a lot of data that needs to be securely stored. Although cloud computing is a useful method for storing IoT data, a lot of data is exposed to security risks and has a significant latency when it is sent from IoT devices to the cloud. Materials and Methods: The proposed work implements an authentication phase and encryption techniques between IoT devices and the cloud in order to address security challenges in IoT-Cloud computing systems. The client-side Elliptic Curve Diffie-Hellman (ECDH) protocol is used by the system to generate a shared secret key that is used to encrypt sensor data using the lightweight encryption method (SPECK). The encrypted data is additionally authenticated using a hashing process, guaranteeing its veracity and accuracy. On the server side, decryption processes are performed using the same encryption algorithms. Results: The results in the last read with data size 9198 Byte show that the system increased the Entropy value to 7.594 and the execution time will be 173 millisecond , and the Throughput is 53.16 . Conclusion: The obtained results of the proposed system are a good value in terms of the performance evaluation parameters such as encryption and decryption time, throughput, and entropy, which makes this algorithm more efficient and more secure.